Comparative analysis of continuous pericapsular nerve group block and supra-inguinal fascia iliaca compartment block for postoperative analgesia in total hip arthroplasty: a randomized controlled trial - Onur Baran; Ayhan Şahin; Cavidan Arar (Journal of Orthopaedic Surgery and Research)
Abstract Background Effective postoperative pain management is essential for recovery after total hip arthroplasty. While opioids are commonly used, their adverse effects necessitate alternative strategies. Peripheral nerve blocks are increasingly utilized, including the pericapsular nerve group block and the supra-inguinal fascia iliaca compartment block. However, comparative data on their efficacy remain limited. This randomized controlled trial evaluated the analgesic effectiveness of these two techniques. The primary outcome was postoperative pain scores at rest and with movement. Secondary outcomes included opioid consumption, the need for rescue analgesia, and hemodynamic stability. Methods Sixty patients undergoing total hip arthroplasty under general anesthesia were randomly assigned to receive either a pericapsular nerve group block or a supra-inguinal fascia iliaca compartment block. Standardized ultrasound-guided techniques were used with equal volumes of local anesthetic. Pain scores were assessed postoperatively using the Visual Analog Scale. Opioid consumption and rescue analgesia use were recorded for twenty-four hours. Results At 12 and 24 h postoperatively, median VAS scores at rest and during movement were significantly lower in the PENG group (≤ 2.0) compared to the SIFICB group (> 4.0) (P < 0.001). Opioid consumption in the first 24 h was significantly lower in the PENG group (11.1 ± 1.5 mg morphine equivalents) than in the SIFICB group (18.4 ± 2.5 mg; P < 0.001). Hemodynamic parameters were stable, with no significant complications. Conclusions The pericapsular nerve group block provided superior analgesia and reduced opioid consumption compared to the supra-inguinal fascia iliaca compartment block. It should be considered a practical component of multimodal pain management for total hip arthroplasty. IRB number Ethics Committee of Tekirdağ Namık Kemal University (2023.06.01.06). Clinical trial registration number https://clinicaltrials.gov (NCT06806865).